(3cJGH GdMTQGJs - (3eMeO dhdj Hf YHO Gddg GdjYbhH, , GdTQja GdJfOZj,J (B1277 (3g` s
(3ChdgG (B:s
(3GdMeO ddg GdPi Ndb GdEfSGf hYdeg GdHjGf , hNdb dg LejY eG ai GdCQV efkG efg haVdkG hEeJfGf CeG HYO , aEfi CjgG GdLGeY eMeO Gdhdi Hf YHO Gddg GdjYbhH GdJOZi CeQge HZQGbI dHf eGJ ajg PHGH hbGd dge Efg fLS s
(3BNQgG (B:s
(3hGdCUM GdPi Ydjg GdEJaGb Cf GdUHGf gh HjV Gdbed dG GdPcQGf , hCf GdPcQ jbGd dg GdTjYHGf hcPG PcQ GdfMd , hbO eQ GfJgi s
(3HgG fXGe GdJYbjHIs
(3fSNI eUMMIs
(3bQf GdfSN (B:s
(3GdbQf GdKGdK YTQs
(3JHUQGJ GdCUd (B:s
(3MGdI GdfSNI SjFI s
Keywords: (3GdcjejGA h GdWHjYjGJs